Systolic excursion of the leaflets of the truncal valve: An unusual mechanism for pulmonary stenosis in common arterial trunk - Saurabh Kumar Gupta; Abhinav Aggarwal; Gurpreet S Gulati; Sivasubramanian Ramakrishnan; Shyam S Kothari; Anita Saxena; Sanjiv Sharma; Balram Airan; Robert H Anderson (Wolters Kluwer Medknow Publications, 2020)
Background: Pulmonary stenosis in patients with common arterial trunk protects the pulmonary vasculature. In our recently published prospective study of common arterial trunk, some patients with sinusal origin of the pulmonary arterial segment had pulmonary stenosis induced by systolic excursion of a truncal valvar leaflet. We aimed to determine the detailed morphologic characteristics of this unusual finding. Methods and Results: All 70 patients underwent echocardiography and computed tomographic angiography as per predefined study protocol. In selected cases, we also performed cardiac catheterization. Among 27 patients with aortic dominance, we found sinusal origin of the pulmonary arterial segment. In 5 of these patients, pulmonary stenosis was induced by systolic excursion of a truncal valvar leaflet. In all these patients, the truncal valve was trisinusate, albeit with asymmetric sinuses. The pulmonary arterial segment arose from the largest left sinus with its relatively large leaflet obstructing the pulmonary orifice during systole. In the remaining 22 patients, without pulmonary stenosis but with sinusal origin of pulmonary arterial segment, the truncal valve was quadrisinusate in 7, bisinusate in 2, and trisinusate in 13. None of the patients with quadrisinusate and bisinusate truncal valves had pulmonary stenosis. Among the 13 patients with trisinusate valves, the sinuses of the truncal valve were symmetrical in 6, while in 7, the pulmonary orifice originated from a smaller asymmetric sinus. Conclusion: Pulmonary stenosis, produced by a relatively large leaflet of an asymmetric truncal sinus, may prevent early development of pulmonary vascular disease. Timely recognition of this unusual mechanism of pulmonary stenosis is important for optimal management.